Solitary Osseous Metastasis of Hepatocellular Carcinoma on SPECT/CT - Sana Munir Gill; Ajeej Ijaz; Aamna Hassan; Hajira Ilyas (Journal of the Pakistan Medical Association, 2024)
Hepatocellular carcinoma (HCC), sixth most common cancer world-over, commonly metastasizes to lung, lymph nodes and adrenal glands. Incidence of osseous metastases in HCC has been reported to be 3-20 % which occurs predominantly in the axial skeleton. It only rarely occurs in the appendicular skeleton and that too as the solitary focus of metastatic deposit.3,4 We present a case of HCC with solitary osseous metastases to the proximal tibia. Keywords: Hepatocellular carcinoma, bone scan, SPECT/CT, osseous metastasis